ANALISIS PERSEPSI PELAKU UMKM TERKAIT QANUN NOMOR 8 TAHUN 2014 TENTANG LEMBAGA KEUANGAN SYARIAH (STUDI KASUS DI KABUPATEN PIDIE, ACEH) - Muhd Syahrul Akbar (Nurul Jadid University, 2024)
In order to realize the kaffah implementation of Islamic law in Aceh, the government made a number of Qanuns, one of which was Qanun No. 8 of 2014 concerning Sharia Financial Institutions. After this Qanun is implemented, all financial institutions operating in Aceh must be based on sharia, including banking institutions. With this Qanun, conventional banks are required to convert into Islamic banks, this of course has an impact on the Acehnese economy, especially for SMEs in Pidie Regency. Pidie is an area where the majority of the people are SMEs. Therefore, researchers are interested in conducting research on the perceptions of MSME actors regarding Qanun No. 8 of 2014 concerning Islamic financial institutions. This research uses descriptive qualitative method, This method was chosen because it was considered suitable for the topic to be studied, this method was able to explain how the actual events occurred in the field. The results of the study show that MSME actors appreciate the government's efforts in realizing a sharia economy through Qanun No. 8 of 2014 concerning Islamic financial institutions, but the government must first prepare and finalize its Islamic financial institutions, so that new problems do not arise, especially for MSME actors after this Qanun is enacted. And for Bank Syariah Indonesia, it is required to continue to improve the quality of its services so that incidents such as not being able to make transfers, payments, and others never happen again.